Advancing Allyship Through Anti-Oppression Workshops for Public Health Students: A Mixed Methods Pilot Evaluation. (December 2021) - Djulus, Gifty; Sheikhan, Natasha Y.; Nawaz, Emin; Burley, Joseph; Thomas-Jacques, Tyla; Naik, Harsh; Warsame, Kahiye; Jamil, Marium; Banerjee, Ananya
This pilot mixed methods evaluation describes the impact of an anti-oppression workshop on allyship development among a group of public health graduate students. After completing a mandatory anti-oppression workshop, a survey including closed- and open-ended questions was administered to 41 public health students specializing in health promotion. Closed-ended questions gathered basic demographic data and Likert-type scale responses to assess changes in participant knowledge, awareness, and attitudes surrounding anti-oppression concepts discussed during the workshop, while open-ended questions asked respondents to reflect on how such changes might influence their development as allies. A response rate of 65.85% (27 respondents) was achieved. The majority of the study group were between the ages of 20 and 24 years (74.07%), self-identified as straight (77.8%), and self-identified as non-White (77.8%), while almost the entire group identified as female (92.59%). Five key themes emerged from a directed content analysis of qualitative data, identifying the importance of anti-oppression workshops for allyship development: conducive environments, positionality, knowledge, active listening and learning, and advocacy. These themes were used to construct a mixed methods joint display for comparative interpretation of quantitative and qualitative data. Mixed methods analysis revealed that anti-oppression workshops can promote allyship development by increasing knowledge of key terms and concepts associated with anti-oppression and facilitating critical reflections on power, privilege, and social location. Our findings demonstrate a profound need for ongoing anti-oppression training among future public health students and professionals.